Evaluation of acepromazine/meperidine/atropine premedication followed by thiopental anesthesia in the cat. - Dyson, D H (1988)
Cardiopulmonary function was assessed in healthy cats premedicated with intramuscular acepromazine, meperidine, atropine combination (premix), followed by induction and maintenance with intravenous thiopental for 30 min. Cardiac output by thermodilution, heart rate, blood pressure and blood gas analysis were evaluated over 120 min. A minor degree of respiratory depression was noted in the cats. Cardiac index (cardiac output/kg) was significantly depressed following thiopental induction and for the entire 120 min studied. Stroke volume was significantly reduced after premix administration and for 90 min posthiopental induction. No significant change in heart rate, systemic vascular resistance or blood pressure was observed. Significant cardiovascular depression was produced by the premedicant, and this persisted following thiopental anesthesia.